Evaluation of U.S. Total Diet Study Data on Selenium. (2015) - Hoffman-Pennesi, Dana; Spungen, Judith; Rabbani, P. Isaac; Briguglio, Stephanie; Wirtz, Mark
Abstract: The potential usefulness of FDA's U.S. Total Diet Study (TDS) selenium (Se) data to the nutrition community was evaluatedas part of the TDS modernization program. TDS Se data collected from 2003 – 2010 was evaluated by comparing these data to Se concentration data in USDA's Standard Reference 26 (SR26) Database. We also evaluated trends in Se concentrations over time and differences in Se concentrations by Market Basket (MB). Comparable SR26 foods were identified for most TDS foods; however, for many TDS foods, there was more than one match in SR26. TDS was found to be a unique source of analytical Se concentration data for four food mixtures and for several SR26 foods with imputed Se concentrations. Se concentrations in TDS foods were similar to analyzed Se concentrations in most corresponding SR26 foods. Se concentrations in whole wheat bread were significantly higher in MB 2 (U.S. West Region, collected in the winter) than in MB 1 (U.S. North Central Region, collected in the fall), 3 (U.S. South Region, collected in the spring), and 4 (U.S. North East Region, collected in the summer). Se concentrations in whole wheat bread were also significantly higher in MB 4 than in MB 3. Se concentrations in boiled eggs were significantly higher in MB 2 than in other market baskets. The U.S. Total Diet Study suspended analysis of Se in 2010, but FDA is evaluating the potential benefits of adding Se analysis back to the TDS program. Results of this study demonstrate the potential value of TDS concentration data for Se and other nutrients to the U.S. nutrition community. However, it is clear that TDS data on generic foods (e.g. tuna, canned in water) are less useful than TDS data on more specifically defined foods (e.g. tuna, white, canned in water). Potential geographical and/or seasonal differences in Se contents of some foods may warrant additional investigation.